Upaya Meningkatkan Hasil Belajar IPA Materi Konduktor dan Isolator Panas Melalui Penerapan Model Pembelajaran Kooperatif Tipe TAI Siswa Kelas VI SDN 03 Pandam Gadang - Sendrawati Sendrawati (Pendidikan Biologi FKIP UMMY, 2021)
This study aims to improve the science learning outcomes of heat conductors and insulators through the application of the TAI type cooperative learning model for the sixth grade students of SDN 03 Pandam Gadang. This type of research is a classroom action research with the research subjects being grade VI students of SDN 03 Pandam Gadang which collects 20 people consisting of 9 male students and 11 female students. This research consists of two cycles with stages 1) planning, 2 ) Action Implementation, 3) Approach, 4) Reflection. The results of the research in my cycle showed that 65% of students had reached the KKM but had not yet reached the indicators of research success. In cycle II, the percentage of students who have achieved the KKM is 80% and has achieved the achievement of research success. Based on the results of the study, it can be said that there is an increase in learning outcomes in science of heat conductors and insulators through the application of the TAI type cooperative learning model for sixth grade students at SDN 03 Pandam Gadang.